Structural Abnormalities in Childhood Absence Epilepsy: Voxel-Based Analysis Using Diffusion Tensor Imaging - Qiu, Wenchao; Gao, Yuan; Yu, Chuanyong; Miao, Ailiang; Tang, Lu; Huang, Shuyang; Hu, Zheng; Xiang, Jing; Wang, Xiaoshan (Frontiers in Human Neuroscience, 2016)
Purpose: Childhood absence epilepsy (CAE) is a common syndrome of idiopathic generalized epilepsy. However, little is known about the brain structural changes in this type of epilepsy, especially in the default mode network (DMN) regions. This study aims at using the diffusion tensor imaging (DTI) technique to quantify structural abnormalities of DMN nodes in CAE patients. Method: DTI data were acquired in 14 CAE patients (aged 8.64±2.59 years, 7 females and 7 males) and 16 age- and sex-matched healthy controls. The data were analyzed using voxel-based analysis (VBA) and statistically compared between patients and controls. Pearson correlation was explored between altered DTI metrics and clinical parameters. The difference of brain volumes between patients and controls were also tested using unpaired t-test. Results: Patients showed significant increase of mean diffusivity (MD) and radial diffusivity (RD) in left medial prefrontal cortex, and decrease of fractional anisotropy (FA) in left precuneus and axial diffusivity (AD) in both left medial prefrontal cortex and precuneus. In correlation analysis, MD value from left medial prefrontal cortex was positively associated with duration of epilepsy. Neither the disease duration nor the seizure frequency showed significant correlation with FA values. Between-group comparison of brain volumes got no significant difference. Conclusion: The findings indicate that structural impairments exist in DMN regions in children suffering from absence epilepsy and MD values positively correlate with epilepsy duration. This may contribute to understanding the pathological mechanisms of chronic neurological deficits and promote the development of new therapies for this disorder.